Ethical Issues in Rehabilitation. A Review of the Conceptualization of Ethical Notions - Goulet, Marie; Drolet, Marie-Josée (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2018)
In rehabilitation, there is a growing interest in ethics. That said, few meta-ethical reflections have been conducted to date. Therefore, a review and critical analysis of the use of the concept of “ethical issue” is warranted. To this end, a systematic and critical review of the literature discussing ethical issues in rehabilitation was conducted. This review, based on the method developed by McCullough and colleagues, identified and analyzed 80 articles. Several characteristics and gaps in the conceptualization of the ethical issue concept were noted. Three main findings emerge from the study: 1) the corpus of texts studied is dominated by descriptive ethics; 2) ethical conceptualisation is marginal, in that ethical concepts are generally stated without being defined; and 3) the corpus is characterized by the use of amalgams and by the multiplication of imprecise ethical concepts that are often used as synonyms while referring to distinct phenomena. These conceptual gaps create conceptual confusion and imprecision that can undermine ethics research, teaching and clinical ethics, and discredit the discipline of ethics.